Direction‐finding measurements of Jovian low‐frequency radio components by Juno near Perijove 1 - Masafumi Imai; William S. Kurth; George B. Hospodarsky; Scott J. Bolton; John E. P. Connerney; Steven M. Levin (Geophysical Research Letters)
Abstract With the aid of the radio and plasma wave (Waves) instrument on board the Juno spacecraft, the first scientific close encounter to Jupiter (Perijove 1) of Juno led to an opportunity to perform direction‐finding measurements of the intense Jovian broadband kilometric (bKOM) radiation at 10 to 142 kHz, two escaping continuum radiation (ECR) events at 9 to 22 kHz, and two narrowband kilometric (nKOM) radiation events at 45–112 kHz. We conclude that the northern bKOM radio sources are localized on M‐shell = 50–60 field lines where M‐shell is similar to L‐shell for nondipolar fields. The beam cone half‐angle varies from 40° to 55°. By intersecting the wave k vector with the Jovian centrifugal equator, two ECR sources are located inside and outside of 11–12 RJ, and two nKOM sources are found between 11 and 20 RJ. These source frequencies and locations can be used for plasma diagnostics in Jupiter's inner magnetosphere.